Rational Design and Experimental Research on the Self-Assembled System of Thermosensitive Molecularly Imprinted Polymers Formed by α-Lipoic Acid and N-Vinyl Caprolactam - Yu-Qin Chen; Bo-Wen Yang; Yun-An Huang; Rui Chang; Qiu-Jin Zhu (International Journal of Polymer Science)
In this paper, the main work was to study the theoretical self-assembly process of thermosensitive molecularly imprinted polymers (MIPs) for α-lipoic acid and to investigate thermosensitive functional monomers through density functional theory calculations (DFT) and intermolecular weak interaction analysis. The M06-2X/6-311+G (d, p) level was used to study the structural parameters, bonding sites, natural population analysis, binding energies (ΔE), atom in molecules (AIM), independent gradient model (IGM), and imprinted molar ratio. The results revealed that α-lipoic acid mainly interacted with N-vinyl caprolactam (NVCL) by weak hydrogen bonds, and the best conditions for MIP synthesis were an optimum molar ratio of 1 : 4 (α-lipoic acid/NVCL). The thermosensitive properties showed that the highest adsorption was at 40°C and the lowest adsorption was at 20°C; also, the MIPs released the intercepted α-lipoic acid inside polymers, and the lower critical solution temperatures (LCST) of MIPs and nonimprinted polymers (NIPs) are 25.7°C and 19.4°C, respectively. In this study, the thermosensitive MIPs displayed a different adsorption capacity towards NVCL, which could be applied for controlled separation and release of α-lipoic acid in different temperatures in a complex matrix.